2015
DOI: 10.3233/jrs-150680
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring drug safety in Astrakhan, Russia

Abstract: The results substantiate the need to continue drug safety monitoring in the Astrakhan region. We plan to further improve the software for ADR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…It is particularly concerning that the international organization pharmacovigilance database has never received any report on clozapine ADRs from Russia 69 . This is not unusual since pharmacovigilance in Russia is very limited 70 . This lack of tradition of pharmacovigilance extends to all drugs, 70 not only to clozapine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly concerning that the international organization pharmacovigilance database has never received any report on clozapine ADRs from Russia 69 . This is not unusual since pharmacovigilance in Russia is very limited 70 . This lack of tradition of pharmacovigilance extends to all drugs, 70 not only to clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…69 This is not unusual since pharmacovigilance in Russia is very limited. 70 This lack of tradition of pharmacovigilance extends to all drugs, 70 not only to clozapine.…”
Section: Clozapine-associated Myocarditis In Russia and Eastern Europementioning
confidence: 99%
“…Прогнозирование НПР -сложный процесс, включающий полноценное и объективное обследование пациента (клинические, лабораторные и инструментальные методы, консультации специалистов) до начала терапии, требующий от врача знаний клинической фармакологии ЛС [33]. Реакции типа А проявляются токсическими симптомами со стороны различных органов и систем и связаны с фармакологическим действием ЛС, они прогнозируемы и их можно предупреждать.…”
Section: прогнозирование и профилактика развития нежелательных побочнunclassified
“…Currently, PMS studies focusing on the assessment of DI reports worldwide are scarce and similarly PMS studies on those reports that are received by the Saudi NPC are lacking. One of the earliest studies focusing on the adverse event reports received by the regional Center for Drug Safety Monitoring (CDSM) in Astrakhan, Russia for the period of 2010 to 2014 found that 1% of ADEs were associated with ineffectiveness of drugs [23]. In 2018 Misu et.al reported that DI (6.4%) was the most frequently reported ADE through the United States Food & Drug Administration Adverse Reporting System (FAERS) database [24], and in South Korea, DI constituted about 1.0 to 1.3% of the ADEs reported to the Korean Adverse Event Reporting System (KAERS) database between 2013 to 2016 [4].…”
Section: Introductionmentioning
confidence: 99%